Framing Disaster Coverage of Earthquakes and Tsunamis on Online Media - Rosemary, Rizanna; Syam, Hamdani M.; Sartika, Maini (TDMRC, Universitas Syiah Kuala, 2023)
Media has a significant role as the source of information for people to prepare for disaster and assist in minimizing disaster risk reduction. Examining how media frame disaster information helps to understand the quantity and quality of the information about the disaster. Earthquakes and Tsunamis in Indonesia are disasters causing massive losses and grieves, and how the media portray and frame the tragedy has influence people's perception and behaviour towards disasters. Since the first significant Earthquake and Tsunami in Aceh 18 years ago, followed by the same disasters in Banten and Palu in 2018, studies have yet to be found analyzing and comparing media coverage of earthquakes and tsunamis within the local media. This study aims to compare how local media frame the information about the Earthquakes and Tsunamis that occurred in Aceh and Palu using the Urs Dahiden framing model to analyze the frame themes in mass media. The findings show more negative coverage of the disasters, focusing more on the numbers of victims, material losses, and the government's incapability to disasters response. Disaster preparedness is framed through the lens of religious perspectives and less on scientific knowledge or how to better respond to future disasters.